1990
DOI: 10.1007/bf01257239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of optic nerve transection upon myelin protein gene expression by oligodendrocytes: evidence for axonal influences on gene expression

Abstract: The effect of optic nerve transection on myelin protein gene expression was studied in rats following axotomy at two ages: during active myelination (17 days of age) and after peak expression of the genes (35 days of age). mRNA levels for proteolipid protein, myelin basic protein and myelin-associated glycoprotein were assessed by northern and dot blotting and by in situ hybridization using tissue sections and cultured individual oligodendrocytes. Transection at 17 days caused down-regulation of mRNAs for prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 38 publications
5
29
0
Order By: Relevance
“…Our data are consistent with those of Kidd et al (1990) and McPhilemy et al (1990), with three exceptions. First, in contrast to Kidd et al (1990) and McPhilemy et al (1990), we found an abrupt drop in steady-state levels that was pronounced by 4 days (see Fig.…”
Section: Regulation Of Plp and Mbp Mrna Expression In Cns Developmentsupporting
confidence: 95%
See 2 more Smart Citations
“…Our data are consistent with those of Kidd et al (1990) and McPhilemy et al (1990), with three exceptions. First, in contrast to Kidd et al (1990) and McPhilemy et al (1990), we found an abrupt drop in steady-state levels that was pronounced by 4 days (see Fig.…”
Section: Regulation Of Plp and Mbp Mrna Expression In Cns Developmentsupporting
confidence: 95%
“…This partially confirms the studies of Kidd et al (1990) and McPhilemy et al (1990). Kidd et al (1990) measured the amounts of PLP, MBP, MAG, and CNP in degenerating rat optic nerves that had been transected at 21 days PN and found a gradual decline in PLP (and MBP) steady-state levels: 15% at 5 days, 50% at 10 days, 60% at 20 days, and 75% at 40 days.…”
Section: Regulation Of Plp and Mbp Mrna Expression In Cns Developmentsupporting
confidence: 84%
See 1 more Smart Citation
“…Some progress has been made in identifying the factors involved in regulating Plp gene expression [Awatramani et al, 1997;Hudson et al, 1997;Jiang et al, 2000]. In vivo studies in rodents have indicated a role for the axon in regulating Plp gene expression [McPhilemy et al, 1990;Dickinson, 1995;Trapp et al, 1997]. These data were strengthened by our observations on cultured murine embryonic spinal cord slices that we grew either attached to substrate or free fl oating.…”
supporting
confidence: 69%
“…Additionally, after myelination has occurred, sustained axonal contact is required to maintain PlpmRNA expression. After optic nerve transection, there is marked downregulation of the Plp gene [McPhilemy et al, 1990], which is mainly due to a reduction in the PlpmRNA population [Dickinson, 1995]. In summary, these data suggest that axons play a major role in regulating Plp gene expression during myelin development and maintenance.…”
Section: Axons Infl Uence Plp Gene Expressionmentioning
confidence: 92%